1998
DOI: 10.1002/(sici)1521-4109(199811)10:16<1137::aid-elan1137>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A Polyaniline-Based Selective Hydrogen Sensor

Abstract: The fabrication and sensor properties of polyaniline-platinum oxide chemoresistors in the presence of combustible gases such as hydrogen, methane, ethylene, acetylene and carbon monoxide is reported. Prior conditioning of the sensors in a hydrogen atmosphere resulted in increased selectivity and sensitivity for hydrogen in air at concentrations between 1000 and 5400 ppm. The conditioned sensors showed negligible response to hydrocarbons and carbon monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…These reactions lead to the protonation of polyaniline nitrogen atoms, resulting in more delocalized charge carriers (polarons and bipolarons) on the backbone for conduction and an increase of the film conductivity. It has also been suggested that the resistance change is caused by the formation of water [25]. The effects of water on the conductivity of polyaniline are well known [26,27] and have been established from nuclear magnetic resonance (NMR) spectroscopy studies that presence of water molecules in the polyaniline facilitates the charge transfer in the polyaniline backbone leading to an increase in polymer's conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…These reactions lead to the protonation of polyaniline nitrogen atoms, resulting in more delocalized charge carriers (polarons and bipolarons) on the backbone for conduction and an increase of the film conductivity. It has also been suggested that the resistance change is caused by the formation of water [25]. The effects of water on the conductivity of polyaniline are well known [26,27] and have been established from nuclear magnetic resonance (NMR) spectroscopy studies that presence of water molecules in the polyaniline facilitates the charge transfer in the polyaniline backbone leading to an increase in polymer's conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, an opposite effect was observed for PPY/Pd composites [78], PANI [79] and PANI/PtO composites [80]. The mechanism of these effects is not clear, however it was suggested that the conductivity increase is caused by formation of water inside the CP film.…”
Section: Conducting Polymers With Affinity To Gasesmentioning
confidence: 97%
“…Composites of CP with metal [78] or metaloxide [63,80,[89][90][91][92][93] nanoparticles, carbon nanotubes [94][95][96], organic and metalorganic [97] compounds and insulating polymers [98][99][100] provide new analytical possibilities. Metaloxide particles are assumed to form n-p hetero junctions with the CP with a depletion region.…”
Section: Conducting Polymers With Affinity To Gasesmentioning
confidence: 99%
“…To enhance the operating of these sensors, composites of CP and metal oxides [46,[128][129][130][131][132][133] and nanoparticles and carbon nanotubes [134][135][136] have been proposed and tested.…”
Section: Affinity To Gases and Vaporsmentioning
confidence: 99%